The Determination of Market Conduct Supervision in Increasing Customer Trust and Sense of Security Mediated by the Customer Satisfaction Index - Naufalia, Viani (Otoritas Jasa Keuangan, 2024)
The objective of this research is to find out how the determinants of market conduct monitoring contribute to fostering customer trust and security, supported by the mediating variable customer satisfaction index. The researcher used quantitative research methods from customers of financial service products in DKI Jakarta, then data analysis techniques used SMART PLS 4.0 application and CSI score calculations. The results of this research show that market conduct monitoring has a significant positive determination in increasing customer confidence by 50.2% and customer sense of security by 25.2%, and can be mediated by a customer satisfaction index of 31.4%.